Management of Large numbers of Student Projects in Computing Degrees - White, Anthony; Censlive, Michael (International Journal For Research In Educational Studies, 2019)
This paper examines the management of large numbers of project students on some computing courses during the period 2001 to 2009, describing the use of management software and procedures to develop, encourage as well as control staff and students. Evidence is provided of a consistent student output despite a rapidly increasing student body, listing the significant issues that arose with the operation of two project modules despite a system with good documentation and supporting material. The distribution of results that were obtained, showed a process where the median grades were consistent for the period of 2001 to 2009 for over 8000 students completing projects in this period. Results show an overall pass rate of 90% for the group project and 86% for the individual project including both academic failures and withdrawal for domestic reasons. This is a report on practice in a rapidly changing environment with lessons and recommendations for the future.